2005
DOI: 10.1103/physrevlett.94.226405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thickness on the Spin Susceptibility of the Two Dimensional Electron Gas

Abstract: Using available quantum Monte Carlo predictions for a strictly 2D electron gas, we estimate the spin susceptibility of electrons in actual devices taking into account the effect of the finite transverse thickness and finding very good agreement with experiments. A weak disorder, as found in very clean devices and/or at densities not too low, just brings about a minor enhancement of the susceptibility.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
81
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 28 publications
10
81
0
Order By: Relevance
“…For the specific sample parameters of Tan et al [11] experiments, we find good agreement with the observed spin susceptibility. Our results are also in good agreement with the QMC simulations of De Palo et al [20] in the same range of coupling strengths.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…For the specific sample parameters of Tan et al [11] experiments, we find good agreement with the observed spin susceptibility. Our results are also in good agreement with the QMC simulations of De Palo et al [20] in the same range of coupling strengths.…”
Section: Introductionsupporting
confidence: 91%
“…Our numerical calculations within both OSA and Dyson approximations are in good agreement with the experimental measurements in the weak and intermediate coupling limits. Furthermore, the level of agreement we obtain is slightly better than QMC simulations [20,31] which do not take the finite thickness effects into account.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations